New Experimental Trends for Phosphoinositides Research on Ion Transporter/Channel Regulation - Masayuki X. Mori; Ryuji Inoue (Elsevier, 2014)
Abstract.: Phosphoinositides(4,5)-bisphosphates [PI(4,5)P2] critically controls membrane excitability, the disruption of which leads to pathophysiological states. PI(4,5)P2 plays a primary role in regulating the conduction and gating properties of ion channels/transporters, through electrostatic and hydrophobic interactions that allow direct associations. In recent years, the development of many molecular tools have brought deep insights into the mechanisms underlying PI(4,5)P2-mediated regulation. This review summarizes the methods currently available to manipulate the cell membrane PI(4,5)P2 level including pharmacological interventions as well as newly designed molecular tools. We concisely introduce materials and experimental designs suitable for the study of PI(4,5)P2-mediated regulation of ion-conducting molecules, in order to assist researchers who are interested in this area. It is our further hope that the knowledge introduced in this review will help to promote our understanding about the pathology of diseases such as cardiac arrhythmias, bipolar disorders, and Alzheimer's disease which are somehow associated with a disruption of PI(4,5)P2 metabolism. Keywords:: phosphoinositide, channel/transporter, PI-turnover, Ca2+ signal, membrane lipid